(untitled) (Journal of Nobel Medical College, 2023)
We present a case of 80 years woman chronic smoker (10 cigarettes)/ per day for 50 years diagnosed with adenocarcinoma in the upper left lobe of her lungs in a geriatric clinic. She has no history of diabetes but taking medicine for hypertension and dyslipidemia. She was admitted and operated on for partial pneumonectomy and discharged after 11 days of care with all essential drugs, and instructions. After 4 weeks of treatment, she complained of unusual polyuria, diagnosed in the department of Geriatrics, Zhongnan Hospital of Wuhan University, China.